2021
DOI: 10.1186/s12967-021-02858-7
|View full text |Cite|
|
Sign up to set email alerts
|

Deconvolution of sarcoma methylomes reveals varying degrees of immune cell infiltrates with association to genomic aberrations

Abstract: Background Soft-tissue sarcomas (STS) are a heterogeneous group of mesenchymal tumors for which response to immunotherapies is not well established. Therefore, it is important to risk-stratify and identify STS patients who will most likely benefit from these treatments. Results To reveal shared and distinct methylation signatures present in STS, we performed unsupervised deconvolution of DNA methylation data from the TCGA sarcoma and an independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…A few studies focused on TME in STS, based on gene expression profiling. This TME is heterogeneous and correlates to histological subtype, even if TAMs and CD8+ T cells are generally the most represented cells ( 76 78 ).…”
Section: The Tumor Microenvironment Of Soft-tissue Sarcomasmentioning
confidence: 99%
“…A few studies focused on TME in STS, based on gene expression profiling. This TME is heterogeneous and correlates to histological subtype, even if TAMs and CD8+ T cells are generally the most represented cells ( 76 78 ).…”
Section: The Tumor Microenvironment Of Soft-tissue Sarcomasmentioning
confidence: 99%
“…Interestingly, it has been frequently shown that TIL levels in DDLPS also range among the highest compared to other STS subtypes [ 86 , 90 , 91 ], which also applies to the percentage of TIL-positive tumors [ 92 ]. Moreover, about 40% of DDLPS represent tumors with high T cell infiltration termed immune-hot [ 93 ].…”
Section: Lps-infiltrating Immune Cell Subsets and Their Clinical Sign...mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified an error in the affiliation 2 for the authors. The incorrect and correct affiliation information is shown below.…”
Section: Correction To: J Transl Med (2021) 19:204 Https://...mentioning
confidence: 99%
“…The incorrect and correct affiliation information is shown below. The author group has been updated above and the original article [ 1 ] has been corrected. Also, affiliation 2 should have been removed as one of the affiliations of the author Benedikt Brors:…”
Section: Correction To: J Transl Med (2021) 19:204 Https://...mentioning
confidence: 99%